First-principles dynamics of collisional intersystem crossing: resonance enhanced quenching of C(1D) by N2. Issue 17 (22nd January 2019) - An, Feng; Han, Shanyu; Hu, Xixi; Xie, Daiqian; Guo, Hua
Abstract : Intersystem crossing is a common and important nonadiabatic process in molecular systems. Revealed with a first-principles investigation, the quenching of C( 1 D) by N2 is efficient due to multiple passages via long-lived collisional resonances, despite relatively small spin–orbit couplings. Abstract : Intersystem crossing is a common and important nonadiabatic process in molecular systems, and its first-principles characterization requires accurate descriptions of both the electronic structure and nuclear dynamics. Here, we report an accurate full-dimensional quantum dynamical investigation of collisional quenching of the excited state C( 1 D) atom to its ground state C( 3 P) counterpart by N2, which is an important process in both combustion and interstellar media, using full-dimensional ab initio potential energy surfaces and spin–orbit couplings. Satisfactory agreement with experimental rate coefficients is obtained. Despite relatively small spin–orbit couplings, it is shown that intersystem crossing is efficient because of multiple passages via long-lived collisional resonances.